Obtenção e caracterização de linhagem de Escherichia coli adaptada ao glicerol bruto proveniente da síntese de biodiesel por engenharia evolutiva - Miranda, Letícia Passos (2016)
Biodiesel is a renewable fuel and its production generate raw glycerol (RG) as main byproduct. The use of RG as carbon source in microorganism cultivations poses as an alternative to add value and reduce the environmental impact of this residue. However, RG impurities (salts, esters, alcohol and soap) can inhibit cell growth. Techniques that aims adapting microorganisms to environments containing contaminants by adaptive evolution have been employed to overcome inhibition problems. Adaptation strategies allows imposing a certain selective pressure upon the population, favoring the appearance of mutants and selection of most beneficial mutations, which will make the cell more suited to develop itself in a hostile environment. This work employed Adaptive Evolution methodology to obtain an E. coli K12 strain adapted to RG concentrated by rotary evaporation (RGRota). Cultivations were carried out in plates (E. coli – USP strain) incubated at 37 ºC, as well as shaken flasks (E. coli – UMinho strain), kept at 37 ºC and 300 rpm, involving transfers to defined media gradually enriched with RGRota. Obtained evolved strain as well as the wild-type strain E. coli – UMinho were characterized in cultivations using 2 L, bench-scale bioreactor, equipped with monitoring and control system. During shaken flask experiments, growth was followed by optical density (OD) readings. In bioreactor cultures, samples were withdrawal to analyze cell concentration of the suspension (OD and dry cell weight), concentrations of glycerol, ethanol and organic acids (liquid chromatography), concentration of viable cells (colony forming units counting) and morphology. Cultures characterization were carried out with E. coli – USP in shaken flasks, the values of maximum specific growth rate (μmax) remained between 0.40 e 0.45 h-1 and they showed little influence of strain or media composition. These results suggest that the selected strain did not have differentiated characteristics from the wild-type strain. For E. coli – UMinho, two adaptation strategies were evaluated: successive transfer during exponential growth phase (OD = ~2.5) and during stationary growth phase (OD = ~10). In both cases cells evolved, showing increased μmax values, with more homogeneous populations being observed for adaptation conducted under the first strategy. After 26 days of adaptation, corresponding to 534 generations, an evolved strain, exhibiting μmax of 0.60 h-1 and capable of growing in medium containing 29 g/L of glycerol from RGRota was selected by the methodology of successive transfers in exponential phase. This growth rate was 27.6 % superior to that achieved by the wild-type strain (0.47 h-1). Evolved and wild-type strains were cultivated in bioreactor, containing defined medium prepared with GBRota to have 40 g/L of glycerol. The evolved one maintained μmáx of 0.61 h-1. Acetate formation was observed, with yield of 0.19 g acetate/g glycerol, which caused growth inhibition and limited biomass yield to 0.26 gbiomass/gglycerol. When the wild-type strain was cultivated in bioreactor, exponential growth started after 24 h of lag phase and it presented μmax of 0.28 h-1, biomass yield of 0,39 gbiomass/gglycerol and acetate yield of 0.19 gacetate/gglycerol. The evolved strain obtained, capable of growing in the biodiesel production residue, showed a μmax value similar to the best results reported in the literature for E. coli adaptation in pure glycerol (0.7 h-1), what demonstrates the successful application of the adaptive evolution methodology. Acetate accumulation can be reduced by Genetic Engineering techniques to manipulate metabolic pathways and this will lead to development of an industrial strain which can be employed as a platform of high value products using unrefined glycerol as substrate.